2013
DOI: 10.1111/jgh.12086
|View full text |Cite
|
Sign up to set email alerts
|

Preserved gastric motility in patients with early gastric cancer after endoscopic submucosal dissection

Abstract: ESD is an effective treatment for EGC both in preserving organs and gastric motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The types of solid tumors included were breast, lung, genitourinary, gynecologic, gastrointestinal, and head and neck cancer, but patients with nonmetastatic papillary thyroid cancer or endoscopically resected early gastric or colon cancer were excluded because patients with these tumors have a relatively high QOL compared to patients with other solid tumors due to minimal major organ dysfunction and a survival rate of nearly 100% with treatments. 34 Patients were recruited from outpatient clinics during their clinic visits for postoperative follow-up, cancer treatment (chemotherapy and/or radiotherapy), or postcancer treatment checkup. Of 233 patients approached, 216 (92.7%) consented to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The types of solid tumors included were breast, lung, genitourinary, gynecologic, gastrointestinal, and head and neck cancer, but patients with nonmetastatic papillary thyroid cancer or endoscopically resected early gastric or colon cancer were excluded because patients with these tumors have a relatively high QOL compared to patients with other solid tumors due to minimal major organ dysfunction and a survival rate of nearly 100% with treatments. 34 Patients were recruited from outpatient clinics during their clinic visits for postoperative follow-up, cancer treatment (chemotherapy and/or radiotherapy), or postcancer treatment checkup. Of 233 patients approached, 216 (92.7%) consented to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…This finding supports our present data. On the contrary, there was no change in the rate of gastric emptying reported after endoscopic submucosal dissection in early gastric cancer patients (6). This observation may be explained by differing effects on the muscle layers, which plays an important role in moving the digested food to the duodenum.…”
Section: Discussionmentioning
confidence: 94%
“…However, Higuchi et al (6) found that endoscopic submucosal dissection preserved gastric emptying in patients with early gastric cancer. Ulcers have been defined histologically as a lesion that penetrates the muscularis mucosae and the muscle layer at the base of the mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that local steroid injection might promote the formation of flat and sufficient granulation tissue without fibrotic contraction, which caused less deformity in the stomach. Higuchi et al [30] investigated whether gastric motility was affected by ESD. Their study revealed that ESD did not significantly affect any of the gastric emptying parameters measured by the [ 13 C]octanoic acid breath test.…”
Section: Complications and Their Preventionmentioning
confidence: 99%
“…Regarding other complications, three studies were identified [28][29][30]. Watari et al [28] investigated the incidence of ''silent'' free air and aspiration pneumonia detected by CT after ESD.…”
Section: Complications and Their Preventionmentioning
confidence: 99%